2021
DOI: 10.3892/ol.2021.12703
|View full text |Cite
|
Sign up to set email alerts
|

LEM domain containing 1 promotes thyroid cancer cell proliferation and migration by activating the Wnt/β‑catenin signaling pathway and epithelial‑mesenchymal transition

Abstract: Thyroid cancer (TC) is the most common type of endocrine malignancy in humans, and its relative incidence has increased continuously in recent years. However, the primary molecular mechanisms of thyroid tumorigenesis and progression remain unclear. Papillary TC (PTC) is the most common subtype of TC. Recent studies have reported that one of the tumorigenesis and progression mechanisms is driven by genetic alterations that regulate the TC cell signaling pathway. In the present study, RNA sequencing (RNA-seq) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies have documented that the emergence of molecular hallmarks is an encouraging advancement for the diagnosis and prognosis of colon cancer and molecular-targeted therapy is pivotal for the treatment of colon cancer [ 35 , 36 ]. The role of LEMD1 has been widely investigated in a variety of human cancers, such as gastric cancer [ 37 ], thyroid cancer [ 19 ], oral squamous cell carcinoma [ 20 , 21 ] and all results implied that LEMD1 may act as a potent oncogene in cancers. What is more, Luo et al have elaborated that LEMD1 involved in competing endogenous RNA mechanism contributes to the development of colorectal cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented that the emergence of molecular hallmarks is an encouraging advancement for the diagnosis and prognosis of colon cancer and molecular-targeted therapy is pivotal for the treatment of colon cancer [ 35 , 36 ]. The role of LEMD1 has been widely investigated in a variety of human cancers, such as gastric cancer [ 37 ], thyroid cancer [ 19 ], oral squamous cell carcinoma [ 20 , 21 ] and all results implied that LEMD1 may act as a potent oncogene in cancers. What is more, Luo et al have elaborated that LEMD1 involved in competing endogenous RNA mechanism contributes to the development of colorectal cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…LEM domain containing 1 (LEMD1), a novel member of CTAs family, has also been reported to participate in various cellular processes. Take cell proliferation for an example, LEMD1 was demonstrated to exacerbate cell proliferation in gastric cancer and thyroid cancer [ 18 , 19 ]. In addition, high expression of LEMD1 is associated with lymph node metastasis and poor prognosis of oral squamous cell carcinoma, and contributes to tumor cell invasion and endothelial transmigration [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al elucidated the promotive roles of LEMD1 in gastric cancer cell growth by the activation of PI3K/AKT signaling [ 6 ]. Xu et al reported that LEMD1 facilitated thyroid cancer cell growth and metastasis via epithelial mesenchymal transition and activation of Wnt/β-catenin signaling [ 29 ]. In this study, due to GSEA, LEMD1 was proved as an upstream positive regulator of the mTORC1 signaling pathway by phosphorylation in PC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most LEM proteins are anchored to membranes via either one (Emerin, LAP2β, LEMD1, ANKLE2) or two (LEMD2, MAN1) transmembrane domains; however, ANKLE1 and LAP2α lack transmembrane domains [21,30,38,39 LEMD1, ANKLE1, and ANKLE2 are less well-characterized and are not localized mainly to the nuclear lamina [38,55]. LEMD1 was identified as a testes-associated gene but has since been found to be overexpressed in a number of malignancies, including colon, thyroid, and prostate cancer, and oral squamous cell carcinoma [56][57][58][59]. One study has expressed epitope-tagged LEMD1 and shown its localization to be apparently extranuclear, possibly associated with the endoplasmic reticulum [39].…”
Section: Nuclear Structure 21 the Nuclear Envelopementioning
confidence: 99%
“…One study has expressed epitope-tagged LEMD1 and shown its localization to be apparently extranuclear, possibly associated with the endoplasmic reticulum [39]. Depletion of LEMD1 in various cancer cell types decreased cell growth, invasiveness, and epithelial-mesenchymal transition [57][58][59]; however, a specific cellular function for LEMD1 has yet to be determined. ANKLE1 is a nonmembrane protein normally located mainly in the cytosol, but able to be actively imported into and exported from the nucleus [38,60].…”
Section: Nuclear Structure 21 the Nuclear Envelopementioning
confidence: 99%